Riociguat in patients with early diffuse cutaneous systemic sclerosis (RISE-SSc): open-label, long-term extension of a phase 2b, randomised, placebo-controlled trial - Distler, Oliver; Allanore, Yannick; Denton, Christopher P; Kuwana, Masataka; Matucci-Cerinic, Marco; Pope, Janet E; Atsumi, Tatsuya; Bečvář, Radim; Czirják, László; Hachulla, Eric; Ishii, Tomonori; Ishikawa, Osamu; et al. (The Lancet. Rheumatology, 2023)
BACKGROUND: The phase 2b Riociguat Safety and Efficacy in Patients with Diffuse Cutaneous Systemic Sclerosis (RISE-SSc) trial investigated riociguat versus placebo in early diffuse cutaneous systemic sclerosis. The long-term extension evaluated safety and exploratory treatment effects for an additional year. METHODS: Patients were enrolled to RISE-SSc between Jan 15, 2015, and Dec 8, 2016. Those who completed the 52-week, randomised, parallel-group, placebo-controlled, double-blind phase were eligible for the long-term extension. Patients originally assigned to riociguat continued therapy (riociguat-riociguat group). Those originally assigned to placebo were switched to riociguat (placebo-riociguat group), adjusted up to 2·5 mg three times daily in a 10-week, double-blind dose-adjustment phase, followed by an open-label phase. Statistical analyses were descriptive. Safety including adverse events and serious adverse events was assessed in the long-term safety analysis set (all patients randomly assigned and treated with study medication in the double-blind phase who continued study medication in the long-term extension). The RISE-SSc trial is registered with ClinicalTrials.gov, NCT02283762. FINDINGS: In total, 87 (72%) of 121 patients in the main RISE-SSc study entered the long-term extension (riociguat-riociguat, n=42; placebo-riociguat, n=45). 65 (75%) of 87 patients were women, 22 (25%) were men, and 62 (71%) were White. Overall, 82 (94%) of 87 patients in the long-term extension had an adverse event; most (66 [76%] of 87) were of mild to moderate severity, with no increase in pulmonary-related serious adverse events in patients with interstitial lung disease. INTERPRETATION: No new safety signals were observed with long-term riociguat in patients with early diffuse cutaneous systemic sclerosis. Study limitations include the absence of a comparator group in this open-label extension study. FUNDING: Bayer and Merck Sharp & Dohme.
Keywords: Patients; mužské pohlaví; Pyrazoles; pyrazoly; ženské pohlaví; Research Design; Humans; Female; Pyrimidines; Male; Scleroderma, Diffuse; výzkumný projekt; pyrimidiny; lidé; pacienti; difuzní sklerodermie